Overproduction and attrition: the fates of songs memorized during song learning in songbirds. (February 2017) - Peters, Susan; Nowicki, Stephen
Abstract : Most songbirds learn their songs through imitation. However, what a male sings as an adult is not necessarily a complete inventory of what he memorized at some earlier point in time: songbirds commonly memorize more material than they eventually sing as adults. Work with swamp sparrows, Melospiza georgiana, first confirmed that males rehearse many of the song models to which they are exposed during the sensory phase of song acquisition but subsequently include only a subset of those rehearsed songs in their adult repertoire. This process of overproduction and selective attrition has since been demonstrated in other species as well. More recently, the persistent memory of tutor songs rehearsed but not included in the adult repertoire has been demonstrated at the neural level. Furthermore, memories of song models heard during the sensory phase of acquisition but never detected during rehearsal in the sensorimotor phase also may persist into adulthood. Here we review behavioural and neural studies of overproduction and attrition in song learning. We discuss factors that may trigger the persistence of some models and the rejection of others in an individual's repertoire and possible functional consequences of this phenomenon. Data from human speech research indicates that humans also may unconsciously retain memories of features of languages heard early in life but never spoken. Highlights: Peter Marler documented overproduction and attrition in swamp sparrow song learning. We review the functional significance of overproduction and attrition. Memories of songs that are not crystallized, or possibly never rehearsed, persist. We review behavioural and neural evidence for these persistent song memories. Humans also retain memories of early language heard early in life but never spoken.